Going With the Flow: An Aid in Detecting and Differentiating Bronchopulmonary Sequestrations and Hybrid Lesions. (10th August 2017) - Oliver, Edward R.; DeBari, Suzanne E.; Giannone, Mariann M.; Pogoriler, Jennifer E.; Johnson, Ann M.; Horii, Steven C.; Gebb, Juliana S.; Howell, Lori J.; Adzick, N. Scott; Coleman, Beverly G.
Abstract : Objectives: To assess the ability of prenatal ultrasound (US) in identifying systemic feeding arteries in bronchopulmonary sequestrations and hybrid lesions and report the ability of US in classifying bronchopulmonary sequestrations as intralobar or extralobar. Methods: Institutional Review Board–approved radiology and clinical database searches from 2008 to 2015 were performed for prenatal lung lesions with final diagnoses of bronchopulmonary sequestrations or hybrid lesions. All patients had detailed US examinations, and most patients had ultrafast magnetic resonance imaging (MRI). Lesion location, size, and identification of systemic feeding arteries and draining veins were assessed with US. Results: The study consisted of 102 bronchopulmonary sequestrations and 86 hybrid lesions. The median maternal age was 30 years. The median gestational age was 22 weeks 5 days. Of bronchopulmonary sequestrations, 66 had surgical pathologic confirmation, and 100 had postnatal imaging. Bronchopulmonary sequestration locations were intrathoracic (n = 77), intra‐abdominal (n = 19), and transdiaphragmatic (n = 6). Of hybrid lesions, 84 had surgical pathologic confirmation, and 83 had postnatal imaging. Hybrid lesion locations were intrathoracic (n = 84) and transdiaphragmatic (n = 2). Ultrasound correctly identified systemic feeding arteries in 86 of 102 bronchopulmonary sequestrations and 79 of 86 hybrid lesions. Of patients who underwent MRI, systemic feeding arteries were reported in 62 of 92 bronchopulmonary sequestrations and 56 of 81 hybrid lesions. Ultrasound identified more systemic feeding arteries than MRI in both bronchopulmonary sequestrations and hybrid lesions ( P  < .01). Magnetic resonance imaging identified systemic feeding arteries that US did not in only 2 cases. In cases in which both systemic feeding arteries and draining veins were identified, US could correctly predict intrathoracic lesions as intralobar or extralobar in 44 of 49 bronchopulmonary sequestrations and 68 of 73 hybrid lesions. Conclusions: Ultrasound is most accurate for systemic feeding artery detection in bronchopulmonary sequestrations and hybrid lesions and can also type the lesions as intralobar or extralobar when draining veins are evaluated.